Analisis Komparasi Panti Wreda Berdasarkan Pelayanan Holistik sebagai Dasar Perancangan Fasilitas Lansia di Surabaya - Natasya Aurelia Putri Mardian; Mufidah Mufidah; Rahman Hakim (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
The elderly population in Indonesia, particularly in Surabaya, has been growing significantly, making the need for facilities serving the elderly increasingly urgent. Elderly rehabilitation services must be provided holistically, covering four main aspects: social, health, psychological, and spiritual. However, the implementation of holistic services in some nursing homes still shows differences in quality and has not fully met the expected standards. This study aims to analyze and compare holistic services in two nursing homes, namely Griya Lansia Husnul Khatimah in Malang and UPTD Griya Wreda Jambangan in Surabaya. The method used in this study is descriptive-qualitative comparison, with a field observation approach and a literature review to establish assessment criteria based on the four aspects of holistic services. The research results show that both nursing homes analyzed have shortcomings in the social and psychological service aspects. This indicates a gap in the quality of services received by the elderly in both homes, which needs attention to ensure that holistic services can be applied more effectively and in line with the established standards. This study is expected to provide recommendations for improving the quality of services in nursing homes in Indonesia.